(untitled) (Historia, 2021)
Petitioning includes the right of individuals directly to request the sovereign or parliament to redress grievances, heed protests, receive advice and consider relevant information, thereby circumventing intermediaries. Thus in the period 1833–1914, although most South African petitions were addressed to the local authorities, some were sent directly to the House of Commons in London, as the ultimate effective apex of the imperial governmental system. Most petitions were concerned with personal grievances against the government, while others were concerned with political advocacy in the form of protest or advice, including substantial supporting information. Only three political issues attracted wider action within the settler society, amounting to concerted campaigns. These were the introduction of representative government in the Cape of Good Hope; opposition to the settlement of transported criminals from the United Kingdom; and support for the maintenance of the established status of the Church of England. From the 1880s, petitions by indigenous Africans raised protests at political developments that affected them negatively, notably political exclusion from parliament. However, the scale of South African petitioning was small and essentially marginal to political discourse in London.